Z Archiwum Instytutu Kultury Polskiej im. Attilia Begeya w Turynie. Fragmenty z listów Romana Pollaka do rodziny Bersano Begey - Szarejko, Sylwia (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
Roman Pollak’s letters held in the archive of the Attilio Begey Institute of Polish Culture in Turin shed some light on the amount of work undertaken in order to found the Institute. The correspondence archived in Turin also testifies to the relationship the Poznan-based professor maintained with the descendants of the renowned Polonophile: Maria, Arturo, Rosina and Marina. Consequently, the article not only discusses Roman Pollak’s involvement in the founding of the Turin Institute, but also presents his relationship with the family of Polonophiles from Piedmont.